From protectionism to inclusion: A New Zealand perspective on health‐related research involving adults incapable of giving informed consent. (18th September 2018) - Douglass, Alison; Ballantyne, Angela
Abstract: The revision of the Council of International Organizations of Medical Sciences (CIOMS) International ethical guidelines for health‐related research (2016) heralds a paradigm shift from the 'protectionist' policies that emerged following historical research atrocities of the 20th century, towards a more nuanced and inclusive approach to research participation. Adopting this modified approach will enable countries to secure the benefits of research for individuals and for society as a whole, while at the same time minimizing the potential for exploitation and research‐related harms. This article considers the potential impact of Guideline 16 of the CIOMS 2016 from a New Zealand perspective, with respect to research involving adults with impaired capacity and who are incapable of giving informed consent. While the CIOMS 2016 apply a 'minimal risk' threshold to guide research involving adults who lack capacity to consent, New Zealand law currently adopts a 'best interests' standard which significantly restricts the scope of permissible research that may be performed in this context. This article argues that the CIOMS 2016 should influence change to New Zealand's legal framework for ethical review of research. CIOMS 2016 provides useful guidance for the necessary standards and processes to enable the responsible and ethical inclusion of adults with impaired capacity in research.